2011
DOI: 10.1111/j.1365-2435.2011.01853.x
|View full text |Cite
|
Sign up to set email alerts
|

Competition between foliar Neotyphodium lolii endophytes and mycorrhizal Glomus spp. fungi in Lolium perenne depends on resource supply and host carbohydrate content

Abstract: Summary1. Cool-season grasses can be simultaneously infected by foliar fungal endophytes and colonised by mycorrhizal fungi, the integrated functions of which are strong predictors of plant fitness within grassland ecosystems. Evidence has been presented previously that infection of grass species with foliar endophytes can negatively affect mycorrhizal colonisation. Here, we tested the hypothesis that mycorrhizal colonisation in turn adversely affects Neotyphodium endophyte concentrations and that the competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 46 publications
2
67
3
Order By: Relevance
“…Although Neotyphodium endophytes occur exclusively in aerial plant tissues, their effects on below-ground processes have been documented (White and Cole 1985;Omacini et al 2004;Jenkins et al 2006). Previous studies, performed on selected agronomic grasses (Schedonorus arundinaceum, L. multiflorum and L. perenne) showed that endophyteinfected plants had lower levels of mycorrhizal colonization (Chu-chou et al 1992;Guo et al 1992;Müller 2003;Omacini et al 2006;Mack and Rudgers 2008;Liu et al 2011) and this was mainly attributed to alkaloid production by endophytes. In contrast, the studies we have conducted in native grasses from Argentina (Novas et al 2005(Novas et al , 2009 showed that roots from endophyte-infected populations displayed a significantly higher frequency of colonisation by mycorrhizal fungi than those free of endophytes.…”
Section: Discussionmentioning
confidence: 94%
“…Although Neotyphodium endophytes occur exclusively in aerial plant tissues, their effects on below-ground processes have been documented (White and Cole 1985;Omacini et al 2004;Jenkins et al 2006). Previous studies, performed on selected agronomic grasses (Schedonorus arundinaceum, L. multiflorum and L. perenne) showed that endophyteinfected plants had lower levels of mycorrhizal colonization (Chu-chou et al 1992;Guo et al 1992;Müller 2003;Omacini et al 2006;Mack and Rudgers 2008;Liu et al 2011) and this was mainly attributed to alkaloid production by endophytes. In contrast, the studies we have conducted in native grasses from Argentina (Novas et al 2005(Novas et al , 2009 showed that roots from endophyte-infected populations displayed a significantly higher frequency of colonisation by mycorrhizal fungi than those free of endophytes.…”
Section: Discussionmentioning
confidence: 94%
“…Production of all three is minimal or undetectable in axenic cultures, but all are produced in significant amounts (of the order of µg/g) in planta [62][64]. Many biotic and abiotic factors influence the production of fungal alkaloids in planta , including mineral stress, for example nitrogen and phosphorous availability [60], [65], [66]. To test if the altered phenotype of ΔsidN 85 infected plants may have an effect on alkaloid production, we determined alkaloid concentrations in infected plants on at least 3 occasions.…”
Section: Resultsmentioning
confidence: 99%
“…There were three replicate plants per strain. Hyphal biomass (expressed as endophyte concentration) was determined by quantitative PCR of the single copy E. festucae NRPS-1 gene (EFM3.005350, http://www.endophyte.uky.edu/) from 1 ng of genomic DNA using a MyiQ™ cycler (Bio-Rad Laboratories, Hercules, California, USA), with primers 1-1F, and 1-1R (Supplementary Table 1) as described (Rasmussen et al, 2007; Liu et al, 2011). Hyphal biomass between strains was compared using one way ANOVA.…”
Section: Methodsmentioning
confidence: 99%